Deepening the EU's Single Market for Services - Ebeke, Christian (IMF Working Papers; Working Paper ;, 2019)
The services sector is increasingly important for the euro area economy, but productivity growth in the sector has stalled over the past two decades. Remaining barriers to cross-border trade in services within the EU Single Market contribute to this weak performance. Our empirical analysis suggests that slow progress in tackling these barriers is associated with political economy factors such as weak government support in parliaments, low government efficiency and high markups. To remove the cross-border restrictions on services trade, we suggest combining incentives such as financial support, technical assistance and improved communication on barriers with more effective enforcement.